Solid precursor-based electrode material surface atom / molecular layer coating preparation method and coating

By dissolving the solid precursor in a solvent and using it in the form of a carrier gas, combined with the non-solid precursor, the problem of low saturated vapor pressure of the solid precursor is solved, which significantly improves the growth efficiency and quality of the surface coating of the lithium-ion battery electrode material, and improves the overall performance of the battery.

CN119725350APending Publication Date: 2025-03-28GUANGDONG YUANNENG TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411538910.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

During atomic/molecular layer deposition, the saturated vapor pressure of the solid precursor leads to too slow coating growth rate or component imbalance, limiting its scale application in surface modification of lithium-ion battery electrode materials.

Method used

By dissolving the solid precursor in a solvent and passing it into the deposition chamber in the form of a carrier gas, after removing the solvent, and combining with the use of the non-solid precursor, a cyclic step is set to improve the deposition efficiency and component control.

Benefits of technology

It significantly improves the deposition efficiency of solid precursors and the precise controllability of the components, mass and thickness of the coating, improves the structure and interface stability of the electrode materials, and improves the comprehensive performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725350A_ABST
    Figure CN119725350A_ABST
Patent Text Reader

Abstract

The invention aims to provide a preparation method of an electrode material surface atom / molecular layer coating based on a solid precursor, which comprises the following steps: firstly, putting an electrode material into a deposition cavity, dissolving the solid precursor into a solvent to obtain a precursor solution, then introducing carrier gas into the precursor solution, and then removing the solvent in the carrier gas; the method comprises the following steps: introducing a carrier gas from which a solvent is removed into a deposition cavity, then purging the deposition cavity with pure carrier gas, finally introducing the carrier gas into a source bottle containing other non-solid precursors, then introducing the carrier gas into the deposition cavity, then purging the deposition cavity with pure carrier gas, and setting cycle steps. The invention further discloses an electrode material surface atom / molecular layer coating based on the solid precursor. The participation degree and the deposition efficiency of the solid precursor are effectively improved, the components, the quality and the thickness of the coating are fully regulated and controlled, the structure and interface stability of the lithium ion battery electrode material is improved, and the comprehensive electrochemical performance such as high specific energy, high safety and long circulation is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and specifically relates to a method for preparing an atomic / molecular layer coating on the surface of an electrode material based on a solid precursor. The present invention also relates to an atomic / molecular layer coating on the surface of an electrode material based on a solid precursor. Background Art

[0002] The continuous development of lithium-ion battery technology has greatly promoted the vigorous development of digital electronics, new energy vehicles, energy storage and other industries. Among them, positive and negative electrode materials play a vital role, fundamentally determining the operating voltage, energy density, cycle life, rate performance, safety, cost and other characteristics of lithium-ion batteries. In recent years, the market has put forward higher requirements for the comprehensive performance of lithium-ion batteries, especially as power batteries need to have high specific energy, high safety, long cycle and other characteristics. Therefore, some high-gram capacity electrode materials, such as high-nickel ternary positive electrode, lithium-rich manganese positive electrode, silicon-based negative electrode, etc., are highly expected; at the same time, all-solid-state batteries, which are recognized as the next generation of battery technology, are also receiving more and more attention. However, various high-gram capacity electrode materials often have problems such as side reactions with electrolytes or solid electrolytes, dissolution of transition metals in electrolytes, insufficient ion or electron conductivity, and poor structural stability during the cycle.

[0003] Atomic layer deposition technology is a modification method that can deposit inorganic functional layers in the form of single atomic films layer by layer on the surface of a substrate or powder. It is applied to the surface coating of lithium-ion battery electrode materials, with significant advantages such as complete coverage, precise thickness, controllable composition, and high repeatability. Adjusting the coating layer from an inorganic film to an organic polymer film or an organic-inorganic hybrid film is the so-called molecular layer deposition technology. A large number of studies have confirmed that the use of atomic / molecular layer technology to prepare one or more uniform functional layers on the surface of positive and negative electrode materials can effectively improve the battery's rate, cycle, safety and other characteristics, and can even solve the matching problem between electrode materials and some solid electrolyte materials.

[0004] Patent CN117154036A discloses a method for preparing a lithium battery positive electrode material with a nano-scale elastomeric molecular protective layer, that is, a surface polyurea film coating with excellent mechanical properties is obtained by surface self-limiting reaction under vacuum conditions based on one or more amine precursors and isocyanate precursors. The prepared coating has good flexibility and electrochemical stability, and its thickness can be precisely controlled by adjusting the source time and number of precursors. It can also selectively add organic metal compound precursors to adjust its physical and chemical properties, ensuring that the volume change of the positive electrode particles is effectively suppressed without destroying the main crystal structure of the positive electrode material, improving the cracking problem of the positive electrode particles, and improving the stability of the positive electrode interface, and finally showing excellent cycle capacity retention and rate performance.

[0005] Patent CN114927650A discloses a method for preparing a silicon-based negative electrode coated with a polymer polyurea coating, that is, preparing a polyurea coating from isocyanate and an amino compound by a molecular layer deposition method. The prepared polyurea coating has good flexibility and electrochemical stability, and its thickness can be precisely controlled at the molecular level through a set cycle period, which effectively buffers the volume expansion of silicon particles, improves the compatibility between silicon and electrolyte, and enhances the interface stability, thereby showing excellent cycle stability and rate performance.

[0006] However, in the atomic / molecular layer deposition process, if one of the precursors used is a solid substance, such as lithium tert-butoxide, aluminum trichloride, niobium pentachloride, p-phenylenediamine, etc., the relatively low saturated vapor pressure will cause the coating growth rate to be too slow, or the stoichiometric ratio with other non-solid precursors will be unbalanced, thus affecting the coating composition and performance, and other problems, which restrict its large-scale application. Therefore, for the atomic / molecular layer deposition technology containing solid substances in the precursor, an effective solution is urgently needed to overcome the disadvantage of the low saturated vapor pressure of the solid precursor, so as to ensure the growth efficiency and quality of the coating and promote its large-scale application in the surface modification of lithium-ion battery electrode materials. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing atomic / molecular layer coatings on the surface of electrode materials based on solid precursors, overcome the disadvantage of too low saturated vapor pressure of solid precursors, effectively improve the participation and deposition efficiency of solid precursors, fully regulate the composition, quality and thickness of the coating, improve the structure and interface stability of lithium-ion battery electrode materials, and ensure comprehensive electrochemical properties such as high specific energy, high safety and long cycle.

[0008] Another object of the present invention is to provide an atomic / molecular layer coating on the surface of an electrode material based on a solid precursor.

[0009] The first technical solution adopted by the present invention is a method for preparing an atomic / molecular layer coating on the surface of an electrode material based on a solid precursor, which is specifically implemented according to the following steps: Step 1: placing the electrode material into a deposition chamber and introducing an inert gas as a carrier gas; Step 2, dissolving the solid precursor in a solvent to obtain a precursor solution, then passing a carrier gas into the precursor solution, and then removing the solvent in the carrier gas; Step 3, passing the carrier gas after the solvent is removed in step 2 into the deposition chamber, and then purging the deposition chamber with pure carrier gas; Step 4, passing the carrier gas into the source bottle containing other non-solid precursors, and then into the deposition chamber, and then purging the deposition chamber with pure carrier gas; Step 5: Set the cycle steps according to the composition and thickness requirements of the atomic / molecular layer coating, regard the complete execution of steps 2 to 4 as one cycle, and set the cycle period.

[0010] The first technical solution of the present invention is also characterized in that: The temperature of the deposition chamber described in step 1 is set to 25~350°C, the deposition chamber pressure is maintained at 100~2000 mTorr, and the electrode material is one or more of nickel-cobalt-manganese ternary, nickel-cobalt-aluminum ternary, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel manganese oxide, and lithium-rich manganese positive electrode materials, or one or more of carbon-based, silicon-based, tin-based, alkali metal-based, and lithium titanate negative electrode materials.

[0011] The carrier gas in step 1 is one or more of nitrogen, argon, and helium, and the flow rate of the carrier gas is 10-500 sccm.

[0012] In step 2, the pulse time is set to 0.1-2 s, the holding time is set to 5-60 s, and the solid precursor is one or more of lithium tert-butoxide, lithium bis(trimethylsilyl)amide, sodium tert-butoxide, ferrocene, ferric chloride, cobaltocene, cobalt iodide, niobium pentachloride, tetrakis(dimethylamino)zirconium, tantalum pentachloride, tantalum pentafluoride, aluminum trichloride, tungsten pentachloride, zinc chloride, titanium tetrachloride, indium chloride, platinum acetylacetonate, p-phenylenediamine, hydroquinone, 2-nitro-1,4-phenylenediamine, oxalic acid dihydrazide, terephthaloyl chloride, terephthalic acid diisocyanate, and 1,4-benzenedithiol.

[0013] In step 2, the solvent is one or more of tetrahydrofuran, acetone, ethyl acetate, benzene, toluene, hexane, ethanol, ether, methyl tert-butyl ether, chloroform, and carbon tetrachloride.

[0014] The solvent removal method in step 2 is any one or more of an adsorbent method, a chemical reaction method, and a distillation method.

[0015] The purge time in step 3 is 10~50 s.

[0016] In step 4, set the pulse time to 0.1~2 s, the pressure holding time to 5~60 s, and the purge time to 10~50 s.

[0017] In step 4, the non-solid precursor is one or more of trimethylaluminum, diethylzinc, zirconium tert-butoxide, pentaethoxyniobium, deionized water, ozone, ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, ethylenediamine, 1,4-diisocyanate, aminoethyl sulfide, tris(2-aminoethyl)amine, diethyltriamine, and triethylenetetramine.

[0018] The second technical solution adopted by the present invention is that the atomic / molecular layer coating on the surface of the electrode material based on the solid precursor is prepared by the method for preparing the atomic / molecular layer coating on the surface of the electrode material based on the solid precursor.

[0019] The beneficial effect of the present invention is that the preparation method of the atomic / molecular layer coating on the surface of the electrode material based on the solid precursor, by pre-dissolving the solid precursor in the solvent, and then loading the carrier gas into the deposition chamber to participate in the atomic / molecular layer deposition process occurring on the surface of the electrode material, can effectively overcome the problems of slow coating deposition rate or component imbalance caused by the low saturated vapor pressure of the solid precursor, and ensure that the solid precursor can participate in the atomic / molecular layer deposition reaction efficiently like other non-solid precursors, thereby ensuring the growth efficiency and quality of the coating. The preparation method of the atomic / molecular layer coating on the surface of the electrode material based on the solid precursor of the present invention can significantly improve the deposition efficiency for the atomic / molecular layer deposition reaction involving more than one solid precursor, ensure the precise control of the film composition, quality, thickness, etc., and then effectively improve the structure and interface stability of the electrode material, and improve the comprehensive performance of the lithium-ion battery. In addition, the preparation method of the atomic / molecular layer coating of the present invention is also conducive to enhancing the selectivity of the precursor material, promoting the low cost of the process, and promoting the scale application of the surface modification technology of the lithium-ion battery electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 These are the implementation steps of a method for preparing an atomic / molecular layer coating on the surface of an electrode material based on a solid precursor proposed by the present invention.

[0021] Figure 2 Example 1, Comparative Example 1 and unmodified LiNi 0.83 Co 0.12 Mn 0.05 O 2 Comparison of scanning electron microscope images of (NCM83) electrode materials.

[0022] Figure 3 The cycle performance of button cells made of Example 1, Comparative Example 1 and unmodified NCM83 electrode materials at 25°C and 1C rate (1C=200 mA / g) is compared.

[0023] Figure 4 The figure is a comparison of the rate performance of button cells made of Example 1, Comparative Example 1 and unmodified NCM83 electrode materials at 25°C.

[0024] Figure 5 The cycle performance of button cells made of Example 1, Comparative Example 1 and unmodified NCM83 electrode materials at 25°C and 1C rate (1C=200 mA / g) is compared. DETAILED DESCRIPTION

[0025] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0026] The present invention first dissolves the solid precursor in a specific solvent to obtain a precursor solution, then passes a carrier gas into the precursor solution, removes the solvent in the carrier gas, and then passes it into a deposition chamber to participate in the atomic / molecular layer deposition process on the surface of the electrode material. This preparation method can significantly improve the deposition efficiency of the solid precursor, ensure the precise control of the coating composition, quality, thickness, etc., and effectively improve the structure and interface stability of the electrode material, and improve the comprehensive performance of the lithium-ion battery; in addition, this preparation method is also conducive to enhancing the selectivity of the precursor material, promoting the low cost of the process, and promoting the large-scale application of the surface modification technology of the electrode material.

[0027] The present invention provides a method for preparing an atomic / molecular layer coating on the surface of an electrode material based on a solid precursor, which is specifically implemented according to the following steps: Step 1, placing the electrode material in a deposition chamber, wherein the temperature of the deposition chamber is set to 25-350° C., an inert gas is introduced as a carrier gas, and the deposition chamber pressure is maintained at 100-2000 mTorr; Step 2, dissolving the solid precursor in a solvent to obtain a precursor solution, then passing a carrier gas into the precursor solution, and then removing the solvent in the carrier gas; Step 3, passing the carrier gas after the solvent is removed in step 2 into the deposition chamber, setting the pulse time to 0.1-2 s, the pressure holding time to 5-60 s, and then purging the deposition chamber with pure carrier gas for 10-50 s; Step 4: Pass the carrier gas into the source bottle containing other non-solid precursors, and then into the deposition chamber, set the pulse time to 0.1-2 s, the pressure holding time to 5-60 s, and then purge the deposition chamber with pure carrier gas for 10-50 s; (Depending on the properties of the solid precursor and the non-solid precursor, step 4 may be performed once or several times before step 2.) Step 5: Set the cycle steps according to the composition and thickness requirements of the atomic / molecular layer coating, and regard the complete execution of steps 2 to 4 as one cycle, and the cycle period is set to 1 to 50 times.

[0028] Steps 2 and 3 are for solid precursors, and step 4 is for non-solid precursors. When making a certain coating, both solid precursors and non-solid precursors are often used, which is a continuous reaction. Step 5 is to repeat the continuous reaction for many cycles (such as 1 to 50 times) according to the required coating thickness.

[0029] The electrode material in step 1 is one or more of nickel-cobalt-manganese ternary, nickel-cobalt-aluminum ternary, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel manganese oxide, and lithium-rich manganese positive electrode materials, or one or more of carbon-based, silicon-based, tin-based, alkali metal-based, and lithium titanate negative electrode materials.

[0030] The carrier gas in step 1 is one or more of nitrogen, argon, and helium, and the flow rate of the carrier gas is 10-500 sccm.

[0031] In step 2, the solid precursor is one or more of lithium tert-butoxide, lithium bis(trimethylsilyl)amide, sodium tert-butoxide, ferrocene, ferric chloride, cobaltocene, cobalt iodide, niobium pentachloride, tetrakis(dimethylamino)zirconium, tantalum pentachloride, tantalum pentafluoride, aluminum trichloride, tungsten pentachloride, zinc chloride, titanium tetrachloride, indium chloride, platinum acetylacetonate, p-phenylenediamine, hydroquinone, 2-nitro-1,4-phenylenediamine, oxalic acid dihydrazide, terephthaloyl chloride, terephthalic acid diisocyanate, and 1,4-benzenedithiol.

[0032] In step 2, the solvent is one or more of tetrahydrofuran, acetone, ethyl acetate, benzene, toluene, hexane, ethanol, ether, methyl tert-butyl ether, chloroform, and carbon tetrachloride.

[0033] The solvent removal method in step 2 is any one or more of an adsorbent method, a chemical reaction method, and a distillation method.

[0034] In step 4, the non-solid precursor is one or more of trimethylaluminum, diethylzinc, zirconium tert-butoxide, pentaethoxyniobium, deionized water, ozone, ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, ethylenediamine, 1,4-butyl diisocyanate, aminoethyl sulfide, tris(2-aminoethyl)amine, diethyltriamine, triethylenetetramine, or one or more of other similar non-solid precursors commonly used in atomic layer / molecular layer deposition.

[0035] The atomic / molecular layer coating on the surface of an electrode material based on a solid precursor is prepared by a method for preparing the atomic / molecular layer coating on the surface of an electrode material based on a solid precursor.

[0036] Example 1 This embodiment is Li-Al-O coated LiNi 0.83 Co 0.12 Mn 0.05 O 2 The preparation method of the (NCM83) positive electrode material, the solid precursor used is lithium tert-butoxide, and the non-solid precursor is trimethylaluminum and deionized water, as follows: Step 1: Place 10 g of NCM83 cathode material into an atomic / molecular layer deposition chamber, raise the chamber temperature to 240 °C, introduce high-purity argon as a carrier gas, and control the chamber pressure at 250-300 mTorr. Step 2, completely dissolving lithium tert-butoxide in tetrahydrofuran, then introducing high-purity argon as a carrier gas, and removing tetrahydrofuran in the carrier gas by adsorption on activated carbon; Step 3, after tetrahydrofuran is removed in step 2, the carrier gas containing lithium tert-butoxide is introduced into the deposition chamber, the pulse time is set to 0.2 s, the pressure holding time is set to 30 s, and then the deposition chamber is purged with high-purity argon gas for 30 s; Step 4: Pass high-purity argon gas into deionized water and then into the deposition chamber, set the pulse time to 0.2 s, the pressure holding time to 30 s, and then purge the deposition chamber with high-purity argon gas for 30 s; Step 5: Pass high-purity argon gas into the detrimethylaluminum and then into the deposition chamber, set the pulse time to 0.2 s, the pressure holding time to 30 s, and then purge the deposition chamber with high-purity argon gas for 30 s; Step 6: Pass high-purity argon gas into deionized water and then into the deposition chamber, set the pulse time to 0.2 s, the pressure holding time to 30 s, and then purge the deposition chamber with high-purity argon gas for 30 s; Step 7: Repeat steps 2 to 6 for 3 cycles.

[0037] The prepared Li-Al-O coated NCM83 cathode material was coated with PVDF binder and conductive carbon black in a mass ratio of 90:5:5, and the surface capacity was controlled at ~1.5 mAh / cm 2 , and then assembled into button cells with Celgard 2500 separator, lithium sheet and commercial carbonate electrolyte for testing.

[0038] Attached Figure 2 The scanning electron microscope photos of the present embodiment and the unmodified NCM83 positive electrode material are shown in Figure 2. There is no significant difference between the two, and the thickness of the coated Li-Al-O coating is about 0.6 nm. The electrode material obtained in this embodiment was prepared into a button cell for testing. Figure 3 As shown in , compared with the unmodified NCM83 positive electrode, the cycle retention rate of the Li-Al-O coated NCM83 positive electrode obtained in this embodiment is significantly improved. Figure 4 It can also be seen that when operating at a higher rate of 2C~5C (1C=200 mA / g), the Li-Al-O coated NCM83 positive electrode obtained in this example also shows obvious advantages over the unmodified NCM83 positive electrode.

[0039] Example 2 This embodiment is a method for preparing a NCM83 positive electrode material coated with a polyurea coating, wherein the solid precursor used is terephthalate diisocyanate and the non-solid precursor is ethylenediamine, as follows: Step 1: Place 10 g of NCM83 cathode material into an atomic / molecular layer deposition chamber, raise the chamber temperature to 75 °C, introduce high-purity nitrogen as a carrier gas, and control the chamber pressure at 200-300 mTorr. Step 2, completely dissolving terephthalate in tetrahydrofuran, and then introducing high-purity nitrogen as a carrier gas, and removing tetrahydrofuran in the carrier gas by adsorption on activated carbon; Step 3, passing the carrier gas containing terephthalate after the tetrahydrofuran is removed in step 2 into the deposition chamber, setting the pulse time to 0.5 s, the pressure holding time to 25 s, and then purging the deposition chamber with high-purity nitrogen for 30 s; Step 4: Pass high-purity nitrogen into ethylenediamine and then into the deposition chamber, set the pulse time to 0.2 s, the pressure holding time to 25 s, and then purge the deposition chamber with high-purity nitrogen for 30 s; Step 5: Repeat steps 2 to 4 for 20 cycles.

[0040] The prepared polyurea coating was coated with the NCM83 positive electrode material, and button cells were made and tested in the same manner as in Example 1. Figure 5 As shown in , compared with the unmodified NCM83 positive electrode, the cycle retention rate of the polyurea coating coated NCM83 positive electrode obtained in this example at 1C rate is significantly improved.

[0041] Example 3 This embodiment is a method for preparing a nano-silicon negative electrode material coated with a polyurea coating, wherein the solid precursor used is terephthalate diisocyanate and the non-solid precursor is ethylenediamine, as follows: Step 1, put 20 g of nano-silicon negative electrode material into the atomic / molecular layer deposition chamber, raise the chamber temperature to 70 ° C, introduce high-purity argon as carrier gas, the carrier gas flow rate is 120 sccm, and the chamber pressure is controlled at 200-300 mTorr; Step 2, completely dissolving terephthalate in tetrahydrofuran, and then introducing high-purity argon as a carrier gas, and removing tetrahydrofuran in the carrier gas by silica gel adsorption; Step 3, passing the carrier gas containing terephthalate after the tetrahydrofuran is removed in step 2 into the deposition chamber, setting the pulse time to 1 s and the pressure holding time to 30 s, and then purging the deposition chamber with high-purity argon gas for 30 s; Step 4: Pass high-purity argon gas into ethylenediamine and then into the deposition chamber, set the pulse time to 0.2 s, the pressure holding time to 30 s, and then purge the deposition chamber with high-purity argon gas for 30 s; Step 5: Repeat steps 2 to 4 for 25 cycles.

[0042] The prepared polyurea coating is coated with nano-silicon anode material, and the electrode is coated with PAA binder, SBR binder, and conductive carbon black in a mass ratio of 92:4:1:3. The surface capacity is controlled at ~1.5 mAh / cm 2 , and then made into button batteries for testing.

[0043] Example 4 This example is Al-Zr-O coated LiNi 0.94 Co 0.04 Mn 0.02 O 2 The preparation method of the (NCM94) positive electrode material, the solid precursor used is tetrakis(dimethylamino)zirconium, and the non-solid precursor is trimethylaluminum and ozone, as follows: Step 1: Place 5 g of NCM94 cathode material into an atomic / molecular layer deposition chamber, raise the chamber temperature to 120 °C, introduce high-purity argon as a carrier gas, and control the chamber pressure at 100-200 mTorr. Step 2: Pass high-purity argon gas into the detrimethylaluminum and then into the deposition chamber, set the pulse time to 0.2 s, the pressure holding time to 25 s, and then purge the deposition chamber with high-purity argon gas for 30 s; Step 3: Mix high-purity argon gas and ozone, and then introduce them into the deposition chamber, set the pulse time to 0.2 s, the pressure holding time to 25 s, and then purge the deposition chamber with high-purity argon gas for 30 s; Step 4, completely dissolving tetrakis(dimethylamino)zirconium in dichloromethane, and then introducing high-purity argon gas as a carrier gas into the dichloromethane, and removing the dichloromethane in the carrier gas by adsorption on activated carbon; Step 5, introducing the carrier gas containing tetrakis(dimethylamino)zirconium after the dichloromethane is removed in step 4 into the deposition chamber, setting the pulse time to 0.5 s, the pressure holding time to 25 s, and then purging the deposition chamber with high-purity argon gas for 30 s; Step 6: Mix high-purity argon gas and ozone, and then introduce them into the deposition chamber, set the pulse time to 0.2 s, the pressure holding time to 25 s, and then purge the deposition chamber with high-purity argon gas for 30 s; Step 7: Repeat steps 2 to 6 for 5 cycles.

[0044] The prepared Al-Zr-O coated NCM94 positive electrode material was made into button cells in the same manner as in Example 1 for testing.

[0045] Comparative Example 1 The experimental conditions of this comparative example, including the positive electrode material, precursor type, chamber temperature and chamber pressure, carrier gas type and flow rate, deposition cycle number, etc., are exactly the same as those in Example 1. The only difference is that the solid precursor lithium tert-butoxide enters the deposition chamber in the following way: lithium tert-butoxide is preheated at 170°C, and then loaded into the deposition chamber with high-purity argon gas, the pulse time is set to 0.2 s, the pressure holding time is 30 s, and then the deposition chamber is purged with high-purity argon gas for 30 s. Afterwards, the prepared Li-Al-O coated NCM83 positive electrode material is made into button cells in the same way as in Example 1 for testing. Attachment Figure 2 The powder scanning electron microscope photos shown in also show no obvious difference, but after the same cycle, the thickness of the Li-Al-O coating is thinner than that in Example 1, about 0.4 nm, indicating that the deposition efficiency of this comparative example is lower than that of Example 1. Figure 3 and attached Figure 4 The button cell cycle and rate performance results also show that although the performance of the Li-Al-O coated NCM83 positive electrode obtained in this comparative example is also improved compared with the unmodified NCM83 positive electrode, the overall effect is not as good as Example 1.

[0046] Comparative Example 2 The experimental conditions of this comparative example, including the positive electrode material, precursor type, chamber temperature and chamber pressure, carrier gas type and flow rate, deposition cycle number, etc., are exactly the same as those of Example 2. The only difference is that the solid precursor terephthalate is introduced into the deposition chamber in the following manner: terephthalate is preheated at 85°C, and then loaded into the deposition chamber with high-purity nitrogen. The pulse time is set to 0.5 s, the pressure holding time is 25 s, and then the deposition chamber is purged with high-purity nitrogen for 30 s. Afterwards, the prepared polyurea coating is coated on the NCM83 positive electrode material, and button cells are made and tested in the same manner as in Example 1. Figure 5 It can be seen that the improvement effect of this comparative example on the cycle performance of the NCM83 positive electrode is not as good as that of Example 2.

[0047] Comparative Example 3 The experimental conditions of this comparative example, including the negative electrode material, precursor type, chamber temperature and chamber pressure, carrier gas type and flow rate, deposition cycle number, etc., are exactly the same as those of Example 3. The only difference is that the solid precursor terephthalate enters the deposition chamber in the following manner: terephthalate is preheated at 85°C, and then loaded into the deposition chamber with high-purity argon gas, the pulse time is set to 1 s, the pressure holding time is 30 s, and then the deposition chamber is purged with high-purity argon gas for 30 s. Afterwards, the prepared polyurea coating is coated with the nano-silicon negative electrode material, and button cells are made and tested in the same manner as in Example 3.

[0048] Comparative Example 4 The experimental conditions of this comparative example, including the positive electrode material, precursor type, chamber temperature and chamber pressure, carrier gas type and flow rate, deposition cycle number, etc., are exactly the same as those of Example 4. The only difference is that the solid precursor tetrakis(dimethylamino)zirconium enters the deposition chamber in the following way: tetrakis(dimethylamino)zirconium is preheated at 50°C, and then loaded into the deposition chamber with high-purity argon gas, the pulse time is set to 0.5 s, the pressure holding time is 25 s, and then the deposition chamber is purged with high-purity argon gas for 30 s. Afterwards, the prepared Al-Zr-O coated NCM94 positive electrode material is made into a button cell for testing in the same way as in Example 1.

[0049] Table 1 summarizes the results of the charge-off test of the atomic / molecular layer surface modified electrode materials prepared in various embodiments and comparative examples. The results of Embodiment 1, Embodiment 2, Embodiment 3, and Embodiment 4 are compared with the results of Comparative Examples 1, Comparative Examples 2, Comparative Examples 3, and Comparative Examples 4, respectively, and it is found that the method for preparing the atomic / molecular layer coating on the surface of the electrode material based on the solid precursor proposed by the present invention has a better improvement effect on the electrode material.

[0050] Table 1. The results of the charge-drop test of the atomic / molecular layer surface modified electrode materials prepared in each embodiment and comparative example

Claims

1. A method for preparing an atomic / molecular layer coating on the surface of an electrode material based on a solid precursor, characterized in that: Follow the steps below to implement it: Step 1: placing the electrode material into a deposition chamber and introducing an inert gas as a carrier gas; Step 2, dissolving the solid precursor in a solvent to obtain a precursor solution, then passing a carrier gas into the precursor solution, and then removing the solvent in the carrier gas; Step 3, passing the carrier gas after the solvent is removed in step 2 into the deposition chamber, and then purging the deposition chamber with pure carrier gas; Step 4, passing the carrier gas into the source bottle containing other non-solid precursors, and then into the deposition chamber, and then purging the deposition chamber with pure carrier gas; Step 5: Set the cycle steps according to the composition and thickness requirements of the atomic / molecular layer coating, regard the complete execution of steps 2 to 4 as one cycle, and set the cycle period.

2. The method for preparing an atomic / molecular layer coating on the surface of an electrode material based on a solid precursor according to claim 1, characterized in that: The temperature of the deposition chamber in the step 1 is set to 25-350°C, the deposition chamber pressure is maintained at 100-2000mTorr, and the electrode material is one or more of nickel-cobalt-manganese ternary, nickel-cobalt-aluminum ternary, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel manganese oxide, and lithium-rich manganese positive electrode materials, or one or more of carbon-based, silicon-based, tin-based, alkali metal-based, and lithium titanate negative electrode materials.

3. The method for preparing an atomic / molecular layer coating on the surface of an electrode material based on a solid precursor according to claim 1, characterized in that: The carrier gas in step 1 is one or more of nitrogen, argon, and helium, and the flow rate of the carrier gas is 10-500 sccm.

4. The method for preparing an atomic / molecular layer coating on the surface of an electrode material based on a solid precursor according to claim 1, characterized in that: In the step 2, the pulse time is set to 0.1-2 s, the holding time is set to 5-60 s, and the solid precursor is one or more of lithium tert-butoxide, lithium bis(trimethylsilyl)amide, sodium tert-butoxide, ferrocene, ferric chloride, cobaltocene, cobalt iodide, niobium pentachloride, tetrakis(dimethylamino)zirconium, tantalum pentachloride, tantalum pentafluoride, aluminum trichloride, tungsten pentachloride, zinc chloride, titanium tetrachloride, indium chloride, platinum acetylacetonate, p-phenylenediamine, hydroquinone, 2-nitro-1,4-phenylenediamine, oxalic acid dihydrazide, terephthaloyl chloride, terephthalic acid diisocyanate, and 1,4-benzenedithiol.

5. The method for preparing an atomic / molecular layer coating on the surface of an electrode material based on a solid precursor according to claim 1, characterized in that: The solvent in step 2 is one or more of tetrahydrofuran, acetone, ethyl acetate, benzene, toluene, hexane, ethanol, ether, methyl tert-butyl ether, chloroform, and carbon tetrachloride.

6. The method for preparing an atomic / molecular layer coating on the surface of an electrode material based on a solid precursor according to claim 1, characterized in that: The solvent removal method in step 2 is any one or more of an adsorbent method, a chemical reaction method, and a distillation method.

7. The method for preparing an atomic / molecular layer coating on the surface of an electrode material based on a solid precursor according to claim 1, characterized in that: The purge time in step 3 is 10 to 50 s.

8. The method for preparing an atomic / molecular layer coating on the surface of an electrode material based on a solid precursor according to claim 1, characterized in that: In step 4, the pulse time is set to 0.1-2 s, the pressure holding time is set to 5-60 s, and the purge time is set to 10-50 s.

9. The method for preparing an atomic / molecular layer coating on the surface of an electrode material based on a solid precursor according to claim 1, characterized in that: The non-solid precursor in step 4 is one or more of trimethylaluminum, diethylzinc, zirconium tert-butoxide, pentaethoxyniobium, deionized water, ozone, ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, ethylenediamine, 1,4-butyl diisocyanate, aminoethyl sulfide, tris(2-aminoethyl)amine, diethyltriamine, and triethylenetetramine.

10. Atomic / molecular layer coating on the surface of electrode material based on solid precursor, characterized in that: The electrode material surface atomic / molecular layer coating is prepared by the method for preparing the electrode material surface atomic / molecular layer coating based on a solid precursor as described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method and application of lithium battery positive electrode material with nanoscale elastomer molecular protective layer

    CN117154036A